Ask Question
14 June, 02:27

Which shows this equation in standard form? 6 - 2 (x - y) = 3x + 5

A) 5x - 2y = 1

B) 5x - 2y = - 1

C) 5x + 2y = 1

D) 2x - 5y = 1

0
Answers (2)
  1. 14 June, 02:50
    0
    standard formis Ax + By = C

    6 - 2 (x-y) = 3x+5

    6 - 2x+2y = 3x+5

    subtract 3x from each side

    6 - 5x + 2y = 5

    subtract 6 from each side

    -5x + 2y = - 1

    divide each side by - 1

    5x - 2y = 1

    A
  2. 14 June, 03:37
    0
    Answer: B

    Step-by-step explanation: 6-2 (x-y) = 3x+5

    6-2x+2y=3x+5

    6+2y=5x+5

    1+2y=5x

    1=5x-2y

    or

    5x-2y=1
Know the Answer?